Studi Golden Section Pada Fasade Bangunan Di Kawasan Kayutangan, Malang - Wulan Astrini; Indyah Martiningrum; Muhammad Satya Adhitama (RUAS (Review of Urbanism and Architectural Studies), 2015)
The study of the golden section in the building facade in Kayutangan, Malang has a specific purpose, namely (1). Evaluate the proportion of building facade in Kayutangan, Malang based on the theory of the golden section and (2). Produce design recommendations of building facade at Kayutangan, Malang which proportionate and in accordance with the golden section. Data collection method using observations of the building facade on both sides of the corridor with a distance meter instrument, then the composition is described as a two-dimensional digitally. Furthermore, the data were analyzed using the golden section proportion, followed by making a digital simulation, especially for building facade that is not in accordance with the proportion of the golden section. The results of this study indicate that the building facade in Kayutangan, Malang has a proportion of 10% of the width and height of the building according to the golden section and 90% are not in accordance with the golden section. The results of this study are expected to be recommendations for structuring the design and aesthetic improvement of the city, particularly in Kayutangan, Malang and can be a reference for those who want to do similar studies in other regions.Keywords: golden section, building facade